Ajuda internacional e crescimento econômico: os condicionantes e efeitos para os países receptores segundo estudos empíricos selecionados - Fetter, Natália Wulff (Universidade do Vale do Rio dos Sinos, 2012)
Since the beginning of the XIXth century the world has been living in an era of economic prosperity and quality of life improvement. In this context of economic growth, there have been different kinds of growth among countries and there are about one in six people in the world that live in extreme poverty. One alternative that has been discussed to reduce poverty is foreign aid and how it can haste this process. The literature mentions several factors as essential to this progress. Thus, from the perspective of possibilities to accelerate economic development and shorten the income inequality, this paper aims to address the international aid as a motivator of progress. Initially, the study assesses the economic growth of less developed countries, especially the issue of poverty, emphasizing the behavior of the African continent. Then foreign aid is delimitated by actors, types and purposes. The literature review also addresses the different ways tested in evaluating the effectiveness of aid in recipient countries by identifying and selecting methods and indicators that explain the relationship between aid and growth.
Keywords: Redução da pobreza; Ajuda internacional; Crescimento econômico; Poverty reduction; Foreign aid; Economic growth; ACCNPQ::Ciências Sociais Aplicadas::Economia